2006
DOI: 10.1258/135763306777889109
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the literature on home monitoring for patients with heart failure

Abstract: We conducted a systematic review of the literature for assessing the value of home monitoring for heart failure (HF) patients. The abstracts of 383 articles were read. We excluded those in which either no home monitoring was done or only the technical aspects of the telemedicine application were described. Forty-two studies met the selection criteria. We classified the results into feasibility (technical and institutional) and impact (on the clinical process, on patient health, on accessibility and acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 31 publications
0
96
0
3
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These showed that evidence of effectiveness was stronger for some conditions (e.g. heart failure) than for others (e.g.…”
Section: Lack Of Evidence About Effectiveness and Cost-effectivenessmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These showed that evidence of effectiveness was stronger for some conditions (e.g. heart failure) than for others (e.g.…”
Section: Lack Of Evidence About Effectiveness and Cost-effectivenessmentioning
confidence: 99%
“…14/26 [8] Assessment of the value of home monitoring for congestive heart failure patients. 13/42 [9] Examination of home monitoring interventions for congestive heart failure patients.…”
Section: Refmentioning
confidence: 99%
“…[6,8] It has been suggested that various telehealth technologies can assist in reducing both burden and cost of CVD around the world. [1,[9][10][11] Various technologies such as remote patient monitoring systems, mobile phone intervention programs, electronic health databases, smartphone apps, instant messaging, video calling and patient portals are just a few of the innovative technology concepts repeatedly used to increase adherence to treatment, disease prevention, and health management programs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, health technologies have also been shown to increase adherence to various treatment and motivation for selfmanagement of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%